2008
DOI: 10.1016/j.bbi.2007.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress and regulation of cellular markers of inflammation in rheumatoid arthritis: Implications for fatigue

Abstract: OBJECTIVES-This study examined whether chronic interpersonal stress is associated with cellular markers of inflammation and regulation of these responses by in vitro doses of glucocorticoids in rheumatoid arthritis (RA) patients. The association between these markers of inflammation and fatigue was also tested.METHODS-Fifty-eight RA patients completed up to 30 daily ratings of the stressfulness of their interpersonal relations. Interleukin-6 (IL-6) production was analyzed in lipopolysaccharide (LPS) stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
107
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 50 publications
4
107
0
8
Order By: Relevance
“…For example, CRP and IL-6 elevations have been shown to accompany ongoing chronic stressors, such as fear of terrorism 16 and caregiving for a relative with dementia, 17 although again there are exceptions. 18,19 The stress-reactive quality of IL-6 and CRP is consistent with data showing that key biologic stress mediators, glucocorticoids and catecholamines, influence cytokine production. 20 Despite having some shared correlates and despite being biologically linked, IL-6 and CRP sometimes independently predict health risk, 21 and other times they show divergent associations with both health outcomes 22 and stress.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…For example, CRP and IL-6 elevations have been shown to accompany ongoing chronic stressors, such as fear of terrorism 16 and caregiving for a relative with dementia, 17 although again there are exceptions. 18,19 The stress-reactive quality of IL-6 and CRP is consistent with data showing that key biologic stress mediators, glucocorticoids and catecholamines, influence cytokine production. 20 Despite having some shared correlates and despite being biologically linked, IL-6 and CRP sometimes independently predict health risk, 21 and other times they show divergent associations with both health outcomes 22 and stress.…”
supporting
confidence: 70%
“…To our knowledge, this has not been evaluated in the context of remitted chronic stress, but ongoing interpersonal stressors persistent for 1-6 months show positive associations with stimulated IL-6 production from PBMCs or whole blood. 18,26 Third, this article evaluates whether relations between past IPV and biologic measures are accounted for by current symptoms of depression and PTSD. Symptoms of both disorders have been associated with elevations in stimulated IL-6 production and IL-6 and CRP circulating levels in some studies.…”
mentioning
confidence: 99%
“…Although many stressors can have this effect, animal and human research has shown that social stressors are particularly strong triggers of inflammation (9)(10)(11). Exposure to everyday social stress in humans, for example, is associated with elevated inflammatory activity (12)(13)(14)(15) and with the up-regulated expression of genes that promote inflammation (16). In addition, controlled laboratory studies have shown that acute social stressors-specifically ones that involve social evaluation and the possibility of social rejection-elicit significant increases in proinflammatory cytokines, a key mediator of the inflammatory response (17,18).…”
mentioning
confidence: 99%
“…Саморегуляция стресс-реализующей системы осуществляется по прин-ципам обратной связи через влияние адренокор-тикотропного гормона (АКТГ), кортизола на структуры головного мозга [2,3]. Внешняя регу-ляция стресс-лимитирующей системы, способной снизить активность стресс-системы, осуществля-ется через центральное влияние ГАМКергиче-ской, опиоидергической и серотонинергической систем.…”
unclassified
“…В регуляции стресс-реакции опре-деленное значение играют эндогенные нейропеп-тиды -субстанция Р и мозговой нейротрофиче-ский фактор (BDNF) [5,6]. Комплекс взаимодей-ствия стресс-запускающих и стресс-лимитирую-щих систем, прямых и побочных эффектов фар-макологических средств, патогенетических про-цессов непосредственно болезни способен вы-звать вторичное иммунодефицитное состояние нейрогенного происхождения [2,[7][8][9][10]. В случае отсутствия адаптационных ресурсов вегетативной регуляции координация эндокринной, иммун-ной, сердечно-сосудистой и пищеварительной си-стем осуществляется с помощью центральных ре-гуляторных механизмов посредством гормонов, нейромедиаторов, иммунотаксических агентов [3,11].…”
unclassified